Pharmacological studies of Neopicrorrhiza scrophularii-flora and its antidiabetic effect - Manandhar, Nayan (Journal of Nepal Pharmaceutical Association, 2015)
Neopicrorrhiza srophulariiflora (NS), locally known as “kutki / katuki” in nepali is available in 3500-4800 m of Nepal. The present study was carried out to evaluate the antidiabetic property of NS in streptozotocin (STZ) induced type 2 diabetic model rats. NS dried rhizomes, was extracted with 80% ethanol and water by cold percolation method. The extracts were administered at a dose of 1.25gkg-1 body weight for 21 consecutive days to type 2 diabetic male Long-Evans rats, bred at BIRDEM animal house. Serum glucose was estimated by GOD PAP method. Ethanol extract of N. srophulariiflora significantly (p<0.05) improved oral glucose tolerance in type 2 rats in comparison to control group. The water extract and ethanol extracts significantly lowered serum glucose level of type 2 diabetic rats in both prandial states (simultaneously with oral glucose load p<0.05; at 75min and 30 minutes prior to oral glucose load p<0.05; at 105min) compared to control group. N. srophulariiflora is beneficial for treating Type 2 diabetes and therefore needs further exploration and researches, both chemically and biologically to identify the active principle(s) and mechanism of action. DOI: http://dx.doi.org/10.3126/jnpa.v27i1.12148 Journal of Nepal Pharmaceutical Association 2014 Vol.XXVII: 34-39